Nurse’s Experience In Playing Role As Assistance Pregnant Women In Semarang - Diah indriastuti; Tahiruddin Tahiruddin; Ani Margawati; Nurullya Rachma; Jeyma Ordonez Sahalul (KLASICS, 2021)
Abstract. The Assistance of pregnant women aims to reduce the incidence of crisis and complications of pregnancy that cause maternal death. This study aims to determine the description of the main duties of nurses in assisting pregnant women using OSOC (One Student One Client) aproach in Semarang. This study aims to determine the main duties of nurses in assisting pregnant women using OSOC (One Student One Client) aproach in Semarang. The design of this study is qualitative with a phenomenological approach. The number of samples for Focus Group Discussion (FGD) was 4 nurses participants. Triangulation participants were 2 midwifes and 1 community health workers.This study shows nurses are still not optimal in carrying out their role in assisting pregnant women because they work in the outpatient health centers within the scope of the treatment center and the implementation of assistance policies for pregnant women does not fully support the nurses. Nurses do not get the main duties structurally assisting pregnant women but still carry out their duties in public health care. This research shows that nurses are able to become partners of pregnant women in assistance.